Financial distress and earnings management: evidence from non-financial companies listed on the Ho Chi Minh Stock Exchange - Nguyen, Viet Dzung; Hoang, Thi Ngoc; Mai, Truong Khanh Linh; Nguyen, Van Cuong (Journal of International Economics and Management, 2024)
The study examines the impact of financial distress on earnings management for Vietnamese non-financial companies. The System Generalized Method of Moments was employed to estimate a dynamic panel data model. Data were collected from non-financial companies listed on the Ho Chi Minh Stock Exchange from 2011 to 2020. The results show that financial distress has a positive impact on earnings management. Specifically, enterprises with good financial health and low risk of bankruptcy tend to make upward profit adjustments, while financially distressed enterprises tend to make downward profit adjustments. This may be due to the supervisory pressure of auditors and creditors, which makes the most affected enterprises no longer have the opportunity to undertake profit manipulation. At the same time, a company with high operating performance tends to maintain profit growth to impress investors in the market. The study results warn policymakers, enterprises, and investors when even financially sound enterprises are incentivized to undertake earnings management. This paper provides additional evidence that financial distress is positively associated with earnings management, which contradicts the findings of some prior studies.